Synergistic Effects of Heavy Metals and Pesticides in Living Systems - Singh, Nitika; Gupta, Vivek Kumar; Kumar, Abhishek; Sharma, Bechan (Frontiers in Chemistry, 2017)
There is a widespread repeated exposure of the population to the pesticides and heavy metals of occupational and environmental origin. Such population is forced to undergo continuous stress imposed by combined exposure of the heavy metals and different classes of the pesticides used in agricultural as well as health practices. The existing reports from several workers have indicated that heavy metals and pesticides in combination may lead more severe impact on the human health when compared to their individual effects. Such a combination of pesticides and heavy metals may also change or influence the detection of exposure. Several studies in past have shown the synergistic toxic effects of heavy metals and pesticides. Such evaluations have revealed the synergistic interactions of various heavy metals and pesticides in animals as well as humans. The aim of the present article is to provide a synthesis of existing knowledge on the synergistic effects of heavy metal and pesticides in living systems. The information included in this article may be useful for different environment protection agencies and policy makers to consider the combined effects of heavy metals and pesticides on humans while designing strategies towards environmental protection and safety regulations about human health.